IMPLEMENTASI KREDIT USAHA RAKYAT (KUR) DALAM PENINGKATAN PENDAPATAN UMKM (Studi pada Bank BSI KCP Sumenep) - Ahmad Zaki Fuadi; Mujibno, Mujibno (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the implementation of the People’s Business Credit (KUR) at Bank Syariah Indonesia (BSI) KCP Sumenep and its impact on increasing the income of micro, small, and medium enterprises (UMKM). BSI was appointed by the government as the KUR distributor in 2023, offering KUR Super Micro, KUR Micro, and KUR Small programs using the murabaḥah contract with a 6% margin, providing financing from 1 million to 500 million rupiah. This study employs a qualitative method, with primary and secondary data collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. Data validity is ensured through triangulation techniques. The results indicate that KUR implementation at BSI KCP Sumenep is carried out through working capital and investment financing for businesses that have been operating for at least six months with good collectibility. Factors contributing to increased income include the entrepreneur’s ability, market conditions, capital, organizational structure, and advertising. The study concludes that KUR serves as an important instrument in supporting UMKM growth by enhancing access to capital and business capabilities.